(untitled) - Hoque, M. Zahidul (Los Banos, Philippines, 1984)
This book includes detailed data-based presentations and discussion of farmers' existing cropping systems and testing of improved cropping patterns and component technologies in eight well-defined agroecological environments.
Keywords: Cropping systems,Farm management